2019
DOI: 10.1002/adfm.201903747
|View full text |Cite
|
Sign up to set email alerts
|

NiMo Solid Solution Nanowire Array Electrodes for Highly Efficient Hydrogen Evolution Reaction

Abstract: Developing high‐performance noble metal–free electrodes for efficient water electrolysis for hydrogen production is of paramount importance for future renewable energy resources. However, a grand challenge is to tailor the factors affecting the catalytic electrodes such as morphology, structure, and composition of nonprecious metals. Alloying catalytic metals can lead to a synergistic effect for superior electrocatalytic properties. However, alloy formation in solution at low synthesis temperatures may result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 34 publications
3
74
0
Order By: Relevance
“…This strict atomic ratio of bivalent and trivalent metal cations in LDHs limits the possible composition of multimetallic alloys. Given the reported excellent HER performance of Ni‐alloys such as NiSn, NiGe, and especially NiMo, there is an urgent need to develop a new method to produce self‐supporting Ni‐alloy nanostructures bypassing the trivalent metal restriction imposed by LDHs. Inspired by the tunable interlayer spacing of layered hydroxide salts (LHS), such as α‐Ni(OH) 2 , through intercalating anions adjustment, we speculate that a second metallic precursor in the form of oxometallate anions may be introduced into the interlayer gallery of LHS, which can then be further reduced to produce Ni‐alloy nanosheets, thus broadening the scope of the emerging LDHs derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…This strict atomic ratio of bivalent and trivalent metal cations in LDHs limits the possible composition of multimetallic alloys. Given the reported excellent HER performance of Ni‐alloys such as NiSn, NiGe, and especially NiMo, there is an urgent need to develop a new method to produce self‐supporting Ni‐alloy nanostructures bypassing the trivalent metal restriction imposed by LDHs. Inspired by the tunable interlayer spacing of layered hydroxide salts (LHS), such as α‐Ni(OH) 2 , through intercalating anions adjustment, we speculate that a second metallic precursor in the form of oxometallate anions may be introduced into the interlayer gallery of LHS, which can then be further reduced to produce Ni‐alloy nanosheets, thus broadening the scope of the emerging LDHs derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst at the same time should be cost effective. Currently many scientific reports therefore focus on the development of more efficient and inexpensive HER catalysts for the cathode side to improve the performance of AWE electrolyzer [10][11][12][13] . Several non-precious metal-based materials, such as transition-metal chalcogenides 14 , carbides 15 and metal alloys 16 , have been widely studied and characterized as HER electrodes.…”
mentioning
confidence: 99%
“…The performance of the porous Ni-Mo alloy microspheres catalyst could be close to that of Pt/C. Interestingly, Nairan et al reported a NiMo solid solution nanowire array electrode synthesized via a facile magnetic field assisted the growth process [89]. The doping of Mo atoms expanded t5.1.1he lattice of surface atoms (d-band shift), and thus, the intrinsic activity of the metal catalyst was significantly improved.…”
Section: Heteroatomic Dopingmentioning
confidence: 95%